Severe Life-Threatening Pregnancy Complications, “Near Miss” and Maternal Mortality in a Tertiary Hospital in Southern Nigeria: A Retrospective Study - Ubong Bassey Akpan; Udeme Asibong; Ezukwa Omoronyia; Kazeem Arogundade; Thomas Agan; Mabel Ekott (Obstetrics and Gynecology International, 2020)
Background. Investigating severe life-threatening pregnancy complications that women encounter and the maternal morbidities (near miss) may help to evaluate the quality of care in health facility and recommend ways to improve maternal and infant survival especially in low-income countries. The aim of this review was to identify, classify, and determine the frequency and nature of maternal near miss events and the maternal and perinatal outcomes. Methods. A retrospective facility-based review of cases of near miss and maternal mortality occurring between 1st January 2012 and 31st December 2016 at the University of Calabar Teaching Hospital was conducted. Near miss case definition was based on the WHO disease specific criteria. The main outcomes included the maternal mortality ratio (MMR), maternal near miss ratio (MNMR), mortality index, maternal morbidities, and perinatal outcome. Results. There were 10,111 pregnancy-related admissions, 790 life-threatening pregnancy complications that resulted in 99 maternal deaths, and 691 near miss cases. The maternal mortality ratio was 979 maternal deaths per 100,000 live births, and the maternal near miss ratio was 6,834 per 100,000 maternities. The MMR to MNMR ratio was 1 : 8. Sepsis and severe anaemia had high case-specific mortality indices of 0.4 and 0.53, respectively. The perinatal outcome was poor compared to that of uncomplicated pregnancies: perinatal mortality rate (PMR) 266 per 1000 live births (OR 7.74); neonatal intensive care (NIC) admissions 11.6 percent (OR 1.83); and low birth weight (LBW) (<2.5 kg) 12.19 percent (OR 1.89). Conclusion. Antenatal care and early recognition of danger signs in pregnancy as well as prompt referral and early institution of essential obstetrics care are important for maternal and infant survival.